Uso de modelagem da informação para planejamento de gestão e manutenção de infraestrutura urbana - Soulé, Pedro Veríssimo (2022)
The operation and maintenance of urban services must be done properly, so that the urban infrastructure reaches its expected useful life. For this, it is necessary to integrate information from the different actors involved in these services, but this usually does not occur. In addition to the difficulty of scale, as these are large areas, cooperative work for infrastructure networks is very complex, as the responsibility for managing the urban space is shared by several actors, and there is no owner responsible for decision-making. The objective of this work is to investigate and discuss how computational tools with Building Information Modeling (BIM) technology and Geographic Information System (GIS) can be used in an integrated way to model urban space information to management infrastructure operation and maintenance. For the development of this research, a computational model of the drainage and sewage networks of the Federal University of São Carlos (UFSCar) campus was created, which served as a case study of an urban environment, as an experimental simulation model. The knowledge acquired by the literature review and the development of the model allowed the elaboration of a proposal of modeling protocols that can be adapted and adopted by public agencies and concessionaires that wish to improve their management and maintenance processes from the use of computational tools. These protocols provide a modular approach to dealing with large urban scales, creating independent BIM bases for the administrators of infrastructure networks and a GIS base as a core for compatibility of all these networks. It was possible to conclude that, considering the current state of technological development, the simple BIM-GIS integration does not constitute a City Information Modeling (CIM) platform. Despite this, the BIM-GIS integration proved to be viable and with great potential to generate an effective increase in assertiveness in the decision-making processes of cities.